How do Inverse Exchange-Traded Funds Targeting Taiwan Shares Track their Underlying Indices? - Lin, Jung-Chu (Asian Economic and Financial Review, 2020)
Amid the tremendous interest of Taiwanese investors in short selling, seven inverse exchange-traded funds (IETFs) targeting the inverse of Taiwan equity benchmark indices were rolled out one after another on the Taiwan market in less than four years. This paper evaluated the tracking performance of these IETFs against their stated return objectives and investigated what factor, fund management issue or market inefficiency, correlated more to performance. The empirical results showed that fund management issues accounted for the majority of the IETFs’ variation in tracking performance, whereas the impact of market inefficiency was relatively small and stable. The study further examined the fundamental determinants of IETFs’ return deviation and discovered that target return volatility, management fee rates, the availability of corresponding futures, share turnover, and turnover rate were influential factors. Among those factors, target return volatility and management fee rates were the two most decisive factors affecting the tracking performance.